Formação continuada de professoras da educação infantil e tdics no contexto pandêmico - Freitas, Renata Cristiane Vinha (2024)
This research advocates for the importance and necessity of integrating new technologies into the continuing education of early childhood teachers. The concern about this topic arose from the working conditions presented by teachers during the COVID-19 pandemic, demonstrating a lack of preparedness for professional actions in this context. With this perspective, this study started with the following research question: To what extent did continuing education courses prepare early childhood teachers to use ICTs (Information and Communication Technologies) during the COVID-19 pandemic? From this question, we aimed to explore and analyze the use of ICTs in continuing education activities and their contributions to the training of early childhood teachers during the COVID-19 pandemic. The research was grounded in authors from the field of the epistemology of practice (Nóvoa, 2019, 2022; Tardif, 2002; Gauthier, 1998), do campo das TDICs (Moran, 2000; Kenski, 2007), and the area of early childhood education (Assis, 2007; Campos, 2006; Kramer, 1994; Kishimoto, 1999; Ostetto, 2011; Pinazza, 2014; Rosemberg, 2012). For data collection, a qualitative study was conducted, starting with a literature review and an exploratory survey using questionnaires with a group of early childhood teachers from a municipal education network in the interior of São Paulo, Brazil, who participated in continuing education courses related to Information and Communication Technologies (ICTs) during the COVID-19 pandemic. Finally, concerning the results obtained, we observed a gap in training processes during the COVID-19 pandemic regarding the use of ICTs. This period represented an unprecedented metamorphosis for the field of education, with many obstacles and difficulties imposed by remote teaching, in which teachers had to reinvent their practices and modes of communication and intervention with their students, especially in early childhood education. Finally, regarding the results obtained, the first point to be highlighted concerns the peculiar period that must be immortalized, facing a Covid-19 pandemic that has transformed society and education systems, prompting a rethink of actions in all social spheres of our country and the world. Another issue concerns a metamorphosis of education systems and teachers' practices in response to the urgency of networks to meet imposed demands and finding some solutions in the use of ICTs and remote assistance. In this panorama, early childhood educators had to reinvent their practices and modes of communication and intervention with peers and children quickly and, in most cases, unprepared due to the lack of mastery in their initial training courses. Remote assistance during the Covid-19 pandemic was not just an emergency response to the crisis; in addition to teachers' learning of ICTs in terms of developing digital skills, they also had the opportunity to rethink and transform practices, generating new meanings and significance in pedagogical activities. Continuing education, based on the perception of these professionals, should be a constant in early childhood education, especially due to the new social and technological demands of the present. Finally, it is important to highlight the importance of coherent policies in the field of teacher training, contributing to professional development and drawing on the production of knowledge from work contexts.